2017
DOI: 10.1016/j.conctc.2016.11.002
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative effectiveness of pediatric integrative medicine as an adjunct to usual care for pediatric inpatients of a North American tertiary care centre: A study protocol for a pragmatic cluster controlled trial

Abstract: BackgroundSome pediatric tertiary care centres in North America supplement conventional care with complementary therapies, together known as pediatric integrative medicine (PIM). Evidence to support the safety and efficacy of PIM is emerging, but the cost-effectiveness of an inpatient PIM service has yet to be assessed.Methods/DesignThis study is a pragmatic cluster controlled clinical trial. Usual care will be compared to usual care augmented with PIM in three pediatric divisions; oncology, general medicine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Large systematic reviews indicate potential cost-effectiveness and even cost savings for IM modalities in adult populations, though higher quality studies are needed [10]. Similar studies have not yet been published for pediatric patients but are currently underway [12].…”
Section: Introductionmentioning
confidence: 99%
“…Large systematic reviews indicate potential cost-effectiveness and even cost savings for IM modalities in adult populations, though higher quality studies are needed [10]. Similar studies have not yet been published for pediatric patients but are currently underway [12].…”
Section: Introductionmentioning
confidence: 99%
“…Study methods will be briefly discussed here; however, a full description of the study methods has been previously published [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The studies that have shown the promise of integrative therapies in the inpatient setting have included yoga, aromatherapy, meditation/relaxation, massage, acupuncture, and nutritional education as treatment modalities. [2][3][4][6][7][8][9][10][11][12][13][14] Despite suggested benefit, there is ambiguity regarding the optimal therapy or a combination of therapies for different clinical conditions, and it is also unclear which medical conditions respond the best to such therapies. An integral part of optimizing high-quality care for patients is knowing the therapies and doses that work for a population, and this cannot be determined with the existing body of literature.…”
Section: Potential Barriers To Implementing Complementary and Integra...mentioning
confidence: 99%
“…CIM encompasses a wide variety of treatment modalities. The studies that have shown the promise of integrative therapies in the inpatient setting have included yoga, aromatherapy, meditation/relaxation, massage, acupuncture, and nutritional education as treatment modalities 2–4,6–14. Despite suggested benefit, there is ambiguity regarding the optimal therapy or a combination of therapies for different clinical conditions, and it is also unclear which medical conditions respond the best to such therapies.…”
Section: Potential Barriers To Implementing Complementary and Integra...mentioning
confidence: 99%
See 1 more Smart Citation